Ex vivo evaluation of a novel through-the-scope traction device for endoscopic submucosal dissection - Alfarone, Ludovico; De Sire, Roberto; Rosenbaum, Boris; Aidibi, Ali; Cellier, Christophe; Hassan, Cesare; Repici, Alessandro; Rahmi, Gabriel; Maselli, Roberta (Endoscopy International Open, 2025)
Endoscopic submucosal dissection (ESD) is a technique used for resection of large neoplastic lesions, providing great oncological outcomes. However, ESD is technically challenging with a long learning curve, high complication rates, and extended procedure times. To address these limitations, various traction-assisted methods have been developed. This study evaluated a novel through-the-scope traction device (TRACMOTION, Fujifilm, Japan), which offers consistent and adjustable traction, in a pilot multicenter randomized ex vivo trial.The study included six endoscopists with limited ESD experience performing ESD on ex vivo porcine stomach models. Participants were randomized into two groups: those using TRACMOTION-assisted ESD (TM-ESD) and those performing conventional ESD (C-ESD). Each trainee completed six procedures, split equally between both groups. The primary outcome was resection speed, whereas secondary outcomes included en bloc, R0 resection rates, perforation rates, and rates of speedy procedures (>20 mm²/min).The TM-ESD group achieved a higher median resection speed of 20.75 mm²/min (95% confidence interval [CI] 14.56–29.25) in comparison to 15.10 mm²/min (95% CI 12.8–16.6) in the C-ESD group (P=0.02). Perforation rates were significantly lower in the TM-ESD group (11.1% (95% CI 0.01–0.34) vs. 61.1% (95% CI 0.35–0.82; P=0.0002). No significant differences were observed in en bloc or R0 resection rates between the groups.TRACMOTION significantly improves the efficiency of ESD, reducing procedure time and complication rates. This traction device could potentially facilitate broader adoption of ESD in clinical practice. However, further research in human trials is necessary to validate these findings.
Keywords: Endoscopy Upper GI Tract; Endoscopic resection (ESD, EMRc, ...); Quality and logistical aspects; Performance and complications; Training